Faktor-Faktor yang Mempengaruhi Keputusan Nasabah Menggunakan Setor Tunai di Anjungan Tunai Mandiri Bank Syariah Indonesia Kota Langsa - Sabilla Ayuni; Khairatun Hisan; Abdul Hamid (JIM: Jurnal Ilmiah Mahasiswa, 2023)
The purpose of this study was to determine the effect of convenience, need, trust and location on customers' decisions to use cash deposit at Bank Syariah Indonesia Automated Teller Machines, Langsa City. This research approach is quantitative. The population in this study were all users of Bank Syariah Indonesia cash deposit ATMs in Langsa City, while the sample used was 75 people. Data collection techniques consist of observation, interviews, questionnaires and documentation. Data analysis techniques include analysis prerequisite tests, classic assumption tests and hypothesis testing. The results of the study show that convenience has a positive and significant effect on customers' decisions to use cash deposits at Bank Syariah Indonesia Automated Teller Machines, Langsa City. This is evidenced by the sig value of the convenience variable, which is 0.035 <0.05 and the tcount value is 2.930 > 1.9944 (ttable). Needs have a positive and significant effect on customers' decisions to use cash deposits at Bank Syariah Indonesia Automated Teller Machines, Langsa City. This is evidenced by the sig value of the needs variable, namely 0.011 <0.05 and tcount 2.616 > 1.9944 (ttable). Trust has a positive and significant effect on customers' decisions to use cash deposits at Bank Syariah Indonesia Automated Teller Machines, Langsa City. This is proven based on the sig value of the trust variable, which is 0.047 <0.05 and the tcount value is 2.935 > 1.9944 (ttable). Location has a positive and significant effect on customers' decisions to use cash deposits at Bank Syariah Indonesia Automated Teller Machines, Langsa City. This is evidenced by the sig value of the location variable, namely 0.020 <0.05 and tcount 3.113 > 1.9944 (ttable). Convenience, need, trust and location simultaneously have a positive and significant impact on customer decisions to use cash deposit at Bank Syariah Indonesia Automated Teller Machines in Langsa City. This is evidenced by the results of the F test obtained sig 0.001 <0.05 and Fcount > Ftable (2.774 > 2.50).